Ten principles for the treatment of post mining landscapes = Dziesięć zasad kształtowania krajobrazów terenów poeksploatacyjnych - Scholz, Brigitte (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
From 2000 to 2010, the Internationale Bauausstellung (IBA) Fürst-Pückler-Land has been active in shaping the post-mining landscape in Lusatia (Brandenburg, East Germany). Based on IBA's experiences, we have formulated ten principles concerning the treatment of post-mining landscapes. The goal is to establish a common understanding for handling post-mining landsapes.
Keywords: kształtowanie krajobrazu; tereny poeksploatacyjne; zagospodarowanie terenów pokopalnianych; rekultywacja; reclamation of degraded areas; sustainable development; regional planning; collaborative planning; industrial heritage; new cultural landscapes